Exploring The Impacts of Mind Mapping Technique on EFL Students’ Writing Performance: A Systematic Literature Review - Gayatri Enok Saraini; Anselmus Sudirman; Johanes Climacus Setyo Karjono; Novita Sumarlin Putri (JELLT (Journal of English Language and Language Teaching), 2025)
This comprehensive study explores the impact of the mind-mapping technique on the writing performance of English as a Foreign Language (EFL) students. It aims to uncover the process, benefits, and challenges of using mind mapping as a pre-writing tool and brainstorming aid. The research methodology involved a systematic review of peer-reviewed international journals indexed in Scopus and the Web of Science. The findings, which cover a wide range of aspects including memory, idea development, organization, and overall writing quality, as well as critical thinking, creativity, and knowledge of vocabulary, grammar, and writing topics, provide a robust understanding of the topic. However, challenges such as time consumption and the learning curve for mastering the technique were identified. This research offers practical significance for educators and sets the stage for future researchers to explore the adaptations of mind-mapping techniques in EFL writing.